Analisis Perhitungan Stroke Per Hour (SPH) produk cross Tube pada PT. Masbi Sukses - Naufal Rafi Muslim; Oleh Oleh (Patria Artha Technological Journal, 2022)
In the development of the times, the industry in Indonesia began to experience rapid development. PT. Masbi Sukses is one of the industrial companies that produces a component in the form of components from four-wheeled and two-wheeled vehicles. Cross tube is one of the products produced at the company PT. Masbi Sukses. Cross tube is a pipe that is used to unite the swing arm on two-wheeled vehicles. The cross tube has a length of 239 mm with a pipe diameter of 28.6 mm and a pipe thickness of 3.2 mm. In this cross tube production process, using a tool called a press machine, this press machine is given a piercing model of pressing dies in order to make holes in the cross tube product as desired. This study aims to determine the stamping process and also analyze the production process time by calculating strokes per hour on cross tube products, with the results in the form of capacity data, takt time data, and problem solving proposals in the form of fish bone diagrams. With the implementation of this research, researchers hope to provide a detailed reference for PT. Masbi Sukses to make improvements or improvisations related to production productivity in the future.